The J2-Immortalized Murine Macrophage Cell Line Displays Phenotypical and Metabolic Features of Primary BMDMs in Their M1 and M2 Polarization State - Spera, Iolanda; Sánchez-Rodríguez, Ricardo; Favia, Maria; Menga, Alessio; Venegas, Francisca C.; Angioni, Roberta; Munari, Fabio; Lanza, Martina; Campanella, Annalisa; Pierri, Ciro L.; Canton, Marcella; Castegna, Alessandra (Cancers, 2021)
Macrophages are immune cells that are important for the development of the defensive front line of the innate immune system. Following signal recognition, macrophages undergo activation toward specific functional states, consisting not only in the acquisition of specific features but also of peculiar metabolic programs associated with each function. For these reasons, macrophages are often isolated from mice to perform cellular assays to study the mechanisms mediating immune cell activation. This requires expensive and time-consuming breeding and housing of mice strains. To overcome this issue, we analyzed an in-house J2-generated immortalized macrophage cell line from BMDMs, both from a functional and metabolic point of view. By assaying the intracellular and extracellular metabolism coupled with the phenotypic features of immortalized versus primary BMDMs, we concluded that classically and alternatively immortalized macrophages display similar phenotypical, metabolic and functional features compared to primary cells polarized in the same way. Our study validates the use of this immortalized cell line as a suitable model with which to evaluate in vitro how perturbations can influence the phenotypical and functional features of murine macrophages.